Histopathological Spectrum of Upper Gastrointestinal Endoscopic Biopsies in a Tertiary care centre - M.L, Anjana; Yevoor, Kavitha (Annals of Pathology and Laboratory Medicine, 2021)
Background: Upper GI endoscopy is an established procedure for investigating a wide range of upper GI conditions especially inflammatory and malignant diseases of stomach and esophagus. A good correlation in diagnosis can be achieved by complementing endoscopic findings with histopathology of biopsy specimens. Methods: Both retrospective and prospective study of upper GI endoscopic biopsy was carried out at department of pathology, KIMS, Hubli during January 2016 to December 2018. Samples were received in 10% formalin; routine processing was followed with H & E staining. Special stain like Giemsa was done for detection of H. Pylori. 396 endoscopic mucosal biopsies were analyzed and evaluated. Result: Out of 396 cases, 250 cases were esophageal biopsies, 104 cases were gastric biopsies & 42 cases were duodenal biopsies. The male: female ratio was 1:9:1. The highest number of cases was seen between 61 to 70 years. Dyspepsia was the common symptom seen in 61.3%. The most common lesions encountered in the esophagus were carcinomas (67%) followed by esophagitis (16%). The commonly encountered gastric lesion was chronic gastritis in 54.8% with H. pylori gastritis being positive in 38.18%. Among the duodenal biopsies, non-neoplastic lesions were most common (59.5%) followed by neoplastic lesions (26%). Conclusion: Upper GI endoscopy is an effective and appropriate preliminary investigation to assess patients with dysphagia, dyspepsia, vomiting. Endoscopy without biopsy is incomplete and that the combination of methods offers a strong diagnostic tool for better patient care.